Knowledge, attitude and practice on leptospirosis among undergraduate students in University Putra Malaysia - Abu Bakar, Siti Maryam; Abdul Rahman, Haliza (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2018)
Introduction: Leptospirosis is an infectious and zoonotic disease caused by pathogenic bacteria called leptospires which can be transmitted through the exposure to the urine or excretion of infected animals, and also water or soil that being contaminated with secretion of the infected animals. Leptospirosis remains a concern in Malaysia, as the number of cases had steadily increased. This study aims to determine the knowledge, attitude and practice (KAP) among final year students of selected programmes in Universiti Putra Malaysia (UPM). Methods: A cross sectional study was conducted among students of Environmental and Occupational Health (ENVOCH) (57 students), Nursing (22 students) and Veterinary Medicine (97 students). Thus, the total sample sizes were 170, however the response rate were 81.76%. Questionnaire was used as the study instrumentation. Results: There was a significant association between race and knowledge, also gender and attitude with p<0.05, (p=0.008) and (p=0.001) respectively. Furthermore, there was also an association between attitude and practice (p<0.05). Meanwhile, there was a significant difference on the knowledge between students of ENVOCH with Veterinary Medicine and Nursing with Veterinary Medicine (p<0.05). Conclusion: Most of the final year students in this study had moderate level of KAP towards Leptospirosis disease. Thus, improvement in education and training must be done to face this issue.